Solid electrolytic capacitor and method of manufacturing same

JP7639698B2Active Publication Date: 2025-03-05NIPPON CHEMI CON CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021565596
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-17
Filing Date
2020-12-15
Publication Date
2025-03-05
Estimated Expiration
2040-12-15

AI Technical Summary

Benefits of technology

【0019】 本発明の固体電解コンデンサは、高い静電容量、低いESR、優れた高周波特性及び高い高温耐久性を示す。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639698000004
    Figure 0007639698000004
  • Figure 0007639698000001
    Figure 0007639698000001
  • Figure 0007639698000002
    Figure 0007639698000002
Patent Text Reader

Abstract

Provided is a solid electrolytic capacitor having high electrostatic capacity, low ESR, excellent high-frequency characteristics, and high high-temperature durability. A solid electrolytic capacitor having: a cathode body 11 having etching pits 11a comprising a valve metal; a cathode 10 having an oxide layer 12 comprising an oxide of the valve metal provided on the surface of the cathode body 11, and a carbon coating layer 13 provided on the surface of the oxide layer 12, the carbon coating layer 13 including carbon particles and having an entry part 13a that enters the etching pits 11a, and a penetration part 13b that penetrates the oxide layer 12 and is conductive with the cathode body 11; an anode having an anode body comprising a valve metal, and a dielectric layer provided on the surface of the anode body and comprising an oxide of the valve metal that constitutes the anode body; and a solid electrolyte layer that includes an electroconductive polymer provided between the carbon coating layer of the cathode and the dielectric layer of the anode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolytic capacitor having a solid electrolyte layer containing a conductive polymer, and a method for manufacturing the same. [Background technology]

[0002] As electronic devices become smaller and faster, capacitors used in power circuits, etc. are required to have high capacitance, low equivalent series resistance (hereinafter, equivalent series resistance is abbreviated as "ESR"), excellent high frequency characteristics, and high high temperature durability. Among electrolytic capacitors that have an anode with an oxide film as a dielectric on the surface of a substrate made of valve metals such as aluminum, tantalum, niobium, etc. and subjected to surface enlargement treatment, an electrolyte that contacts the oxide film and acts as a true cathode, and a cathode (apparent cathode) made of a valve metal in contact with the electrolyte, solid electrolytic capacitors that use conductive polymers with high conductivity and high thermal decomposition temperature derived from monomers with π-conjugated double bonds such as substituted or unsubstituted thiophene, pyrrole, aniline, etc. as electrolyte (hereinafter, solid electrolytic capacitors using conductive polymers as electrolytes will be simply referred to as "solid electrolytic capacitors") are suitable for meeting the above requirements.

[0003] In a solid electrolytic capacitor, a natural oxide film is generally present on the surface of the cathode made of valve metal, even if no treatment to provide an oxide film is performed. Therefore, the capacitance (C) of a solid electrolytic capacitor is the composite capacitance of the anode capacitance (Ca) and the cathode capacitance (Cc), as shown in the following formula. Even if the anode capacitance is increased by etching, the capacitance of the capacitor will be smaller than the anode capacitance as long as the cathode has capacitance.

number

[0004] Therefore, in order to increase the cathode capacity of solid electrolytic capacitors, etching has been performed on the cathode valve metal foil. However, if etching is excessive, the surface of the valve metal foil dissolves at the same time, which prevents the increase in the surface area ratio, and an oxide film is easily formed on the surface of the valve metal foil, so there is a limit to how much the cathode capacity can be increased and maintained by etching. Therefore, a method has been proposed in which a film of a conductive material that is less likely to form an oxide film is formed on the surface of the cathode valve metal foil, thereby increasing the cathode capacity and suppressing the growth of the oxide film.

[0005] For example, Patent Document 1 (JP Patent Publication 2000-114109A) discloses a solid electrolytic capacitor equipped with a cathode foil in which a chemical conversion oxide film is formed on the surface of an etched valve metal foil, and a film made of a metal nitride such as TiN, ZrN, or TaN, which is difficult to form an oxide film, is further formed thereon by a vapor deposition method. It is explained that the cathode capacity becomes infinite because a part of the chemical conversion oxide film is removed by vapor deposition of the metal nitride, and the metal nitride and the valve metal foil are electrically connected, and the capacitance (C) of the capacitor expressed by the above formula becomes equal to the anode capacity (Ca) and reaches a maximum. It is specifically shown that a capacitor in an example using a cathode foil with a TiN film formed on the chemical conversion oxide film has a higher capacitance and a lower dielectric loss than a capacitor in a comparative example using a cathode foil with only a chemical conversion oxide film formed thereon. In addition, Patent Document 2 (JP Patent Publication 2005-109272 A) discloses a solid electrolytic capacitor equipped with a cathode foil in which a chemical oxide film is formed on the surface of an etched valve metal foil, and a film made of a metal carbide with low specific electrical resistance such as TiC, WC, or ZrC is further formed thereon by a vapor deposition method, and explains that the low specific electrical resistance of the metal carbide brings the conductive polymer and the cathode foil into a conductive state, maximizing the combined capacitance of the capacitor, and that the adhesion between the metal carbide and the conductive polymer is good, thereby reducing the ESR. It is specifically shown that a capacitor in an example using a cathode foil with a TiC film has a higher capacitance and a lower ESR than a capacitor in a comparative example using a cathode foil with a TiN film instead of a TiC film.

[0006] It has been pointed out that the solid electrolytic capacitors disclosed in Patent Documents 1 and 2 have a problem in that an oxide film gradually grows on the surface of the metal nitride or metal carbide of the cathode, decreasing the capacitance of the capacitor. In order to solve this problem, a method of using a carbon film instead of the metal nitride or metal carbide film has been proposed. For example, Patent Document 3 (JP Patent Publication 2006-190878 A) discloses a solid electrolytic capacitor equipped with a cathode in which a carbon film is formed on the surface of a valve metal by a dry plating method such as an ion plating method, and explains that since the carbon film is fixed to the surface of the valve metal and an oxide film is not formed on the valve metal, the cathode capacity approaches almost infinity and the capacitor capacity is only the anode capacity. It has been shown that when a cathode foil in which a carbon film is formed by an ion plating method on an etched aluminum foil is used, the capacitance of the solid electrolytic capacitor at 120 Hz is higher than when an aluminum foil without a carbon film is used as the cathode foil. Also, a technique for forming a carbon film by a coating method is known. For example, Patent Document 4 (JP Patent Publication 2007-095865 A) discloses a method for manufacturing an aluminum cathode foil for an electrolytic capacitor in which a metal film such as Ti is formed on the surface of a roughened aluminum material and carbon particles are fixed on the upper layer side of the metal film. In the examples, a Ti film is formed on an etched aluminum foil by vacuum deposition or sputtering, and then a coating material in which carbon particles are dispersed in an organic binder is applied and heated to form the cathode foil. In addition, as a comparative example, a cathode foil formed by directly applying the coating material on an etched aluminum foil and heating it is also shown. In the examples and the comparative example, almost the same electrostatic capacitance is obtained, except for the change in capacitance before and after chemical conversion treatment assuming the application of a reverse voltage. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2000-114109 A [Patent Document 2] JP 2005-109272 A [Patent Document 3] JP 2006-190878 A [Patent Document 4] JP 2007-095865 A Summary of the Invention [Problem to be solved by the invention]

[0008] Although solid electrolytic capacitors have the advantages of being small, large capacity, low ESR, and easy to form into chips, the capacitance of capacitors has generally been evaluated under the condition of 120 Hz, and evaluation in the high frequency range has been insufficient. Therefore, the inventors measured the capacitance at 10 kHz of prior art solid electrolytic capacitors having a cathode with a titanium carbide film, a carbon vapor deposition film, or a carbon coating film, and found that all of the capacitors showed relatively low capacitance and needed to be improved. In addition, when the ESR of the above solid electrolytic capacitors was measured under the condition of frequencies of 10 kHz and 100 kHz, all of the capacitors showed relatively high ESR values. On the other hand, as mentioned above, solid electrolytic capacitors are now required to have high capacitance, low ESR, excellent high frequency characteristics, and high high temperature durability.

[0009] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a solid electrolytic capacitor that can meet the above-mentioned requirements. [Means for solving the problem]

[0010] The applicant, in PCT / JP2019 / 022741, which was unpublished at the time of filing the application on which the priority claim of this application is based, discloses an electrode body used in the cathode of an electrolytic capacitor exhibiting good capacity, which comprises a cathode body made of a valve metal and having a surface expansion layer formed thereon, and a carbon layer formed on the surface expansion layer, and the boundary between the surface expansion layer and the carbon layer has an uneven shape, and also discloses a method for manufacturing an electrode body having suitable performance, in which a slurry containing carbon particles is applied to the surface of the cathode body, dried, and then pressed. When this method is carried out using an etched aluminum foil as a substrate, the pressing process can push the carbon particles into the etching pits of the aluminum foil, and the carbon particles can break through the oxide film on the aluminum foil to establish electrical conductivity between the carbon coating layer and the aluminum of the substrate.

[0011] Although PCT / JP2019 / 022741 describes in detail the performance of a wet electrolytic capacitor using the above-mentioned electrode body as a cathode, it does not describe the performance of a solid electrolytic capacitor using the above-mentioned electrode body as a cathode. The inventors created a solid electrolytic capacitor using the electrode body having the above-mentioned preferable performance as a cathode and evaluated the performance of the obtained capacitor. It was confirmed that not only the capacitance at a frequency of 120 Hz but also the capacitance at a frequency of 10 kHz increased, and both the ESR at a frequency of 10 kHz and the ESR at 100 kHz significantly decreased, and even after a charge / discharge test was performed under a high-temperature condition of 105 ° C. as a durability test, there was little change in the capacitance and ESR of the capacitor, and thus the present invention was achieved.

[0012] Therefore, the present invention first provides a cathode comprising: a cathode substrate made of a valve metal and having an etching pit; an oxide layer made of an oxide of the valve metal provided on a surface of the cathode substrate; and a carbon coating layer provided on a surface of the oxide layer, containing carbon particles, and having an entry portion that enters the etching pit and a penetration portion that penetrates the oxide layer and is electrically connected to the cathode substrate; an anode having an anode substrate made of a valve metal and a dielectric layer made of an oxide of the valve metal constituting the anode substrate and provided on a surface of the anode substrate; a solid electrolyte layer including a conductive polymer and disposed between the carbon coating layer of the cathode and the dielectric layer of the anode; The present invention relates to a solid electrolytic capacitor comprising:

[0013] The present invention also provides a method for producing the solid electrolytic capacitor, comprising the steps of: a coating step of coating a surface of an oxide layer made of an oxide of a valve metal provided on a surface of a cathode substrate made of a valve metal and having etching pits, and drying the carbon slurry to form a slurry layer; and a pressing step of applying a pressing treatment to the slurry layer to press the carbon particles into the etching pits and cause the carbon particles to break through the oxide layer, thereby forming a carbon coating layer having an intrusion portion intruding into the etching pits and a penetration portion penetrating the oxide layer and conducting to the cathode substrate, an anode forming step of forming a dielectric layer by oxidizing the surface of an anode substrate made of a valve metal; an electrolyte forming step of forming a solid electrolyte layer containing a conductive polymer between the carbon coating layer of the cathode and the dielectric layer of the anode; The present invention relates to a method for producing a solid electrolytic capacitor, comprising the steps of:

[0014] The etching pits in the cathode substrate may be tunnel pits or spongy pits, or may be through-type pits or residual-core type pits, and the oxide layer provided on the surface of the cathode substrate may be a chemical oxide film or a natural oxide film. In this specification, the portion of the cathode excluding the carbon coating layer may be referred to as the "current collector".

[0015] In the pressing step in the cathode formation process, when pressure is applied to the slurry layer, the carbon particles break through the oxide layer and are electrically connected to the cathode substrate, forming a through-hole in the carbon coating layer, and the carbon particles are pushed into the etching pits to form an intrusion in the carbon coating layer. When the average length of the intrusion in the carbon coating layer is 1 / 5 or more, preferably 1 / 4 or more, of the average length of the etching pits, the adhesion between the carbon coating layer and the current collector in contact with the carbon coating layer is suitably maintained, the interfacial resistance between the carbon coating layer and the current collector is reduced, and peeling of the carbon coating layer is suitably suppressed. Here, the "length of the etching pit" means the length from the opening position of the etching pit to the bottom when the cathode substrate has a through-type etching pit, which is equal to the thickness of the cathode substrate, and when the cathode substrate has a residual-core type etching pit, which is indicated by the symbol Ha in the example shown in FIG. 1. In addition, the "length of the intrusion in the carbon coating layer" means the length from the opening position of the etching pit in the intrusion to the position furthest from the opening position, which is indicated by the symbol Hb in the example shown in FIG. 1. The average of these values ​​can be obtained by looking at a 5000x magnification SEM photograph of the cross section of the cathode and averaging the values ​​obtained for each etch pit and intrusion.

[0016] The pressure in the pressing step in the cathode formation process is set so that the interface resistance of the cathode is 10 mΩcm 2 Less than 6mΩcm, preferably 2 Less than 3mΩcm, more preferably 2 In the pressing step, the interface resistance is preferably adjusted to 10 mΩcm or less. 2By setting as follows, it is possible to suitably ensure the conduction between the carbon coating layer and the cathode substrate and the adhesion between the carbon coating layer and the current collector. The "interface resistance at the cathode" means the interface resistance depending on all interfaces included in the cathode, measured between the carbon coating layer and the cathode substrate, and can be obtained by a known measurement method, for example, by the following method. First, a cathode having a carbon coating layer with a thickness of 20 to 30 μm is formed. Next, a probe having an array of a plurality of measurement test needles for measuring the potential of the surface of the carbon coating layer at many positions and an array of application test needles for applying a current to the cathode provided around this array is brought into contact with the surface of the carbon coating layer, and a predetermined direct current is applied between the application test needles, and the potential generated on the surface of the carbon coating layer when the current is applied is measured at many positions by the measurement test needles, thereby obtaining an actual measurement value of the potential distribution. Next, a model equation is constructed in which the actually measured thickness of the current collector, the resistance of the current collector, and the thickness of the carbon coating layer are fixed values, and the resistance and interface resistance of the carbon coating layer are variables, and the potential distribution in the model equation is calculated while changing the variables. The interface resistance when the calculated potential distribution value obtained from the model formula and the measured potential distribution value match is the "interface resistance in the cathode". An example of a suitable device for obtaining the interface resistance in the cathode is the electrode resistance measurement system RM2610 manufactured by Hioki Electrochemical Co., Ltd. The thickness of the carbon coating layer is not particularly limited as long as the oxide layer and the surface of the cathode base to be coated with the carbon coating layer are entirely coated, and it can be, for example, an average thickness of 0.5 to 30 μm. In the measurement method using the above-mentioned potential distribution, a carbon coating layer with a thickness of 20 to 30 μm is used, but the value of the interface resistance in the cathode obtained by pressing a thinner carbon coating layer with the same pressure is similar to the value of the interface resistance in the cathode equipped with a carbon coating layer with a thickness of 20 to 30 μm.

[0017] The carbon coating layer of the solid electrolytic capacitor of the present invention has an entry part that enters the etching pit of the cathode substrate, and therefore naturally contains at least carbon particles having a particle size that can enter the etching pit, but in a preferred embodiment of the present invention, the carbon coating layer also contains carbon particles having a particle size that cannot enter the etching pit, and therefore the carbon slurry used in the coating step of the cathode formation process also contains carbon particles having a particle size that cannot enter the etching pit. Although only a part of the particles may enter the etching pit, the whole of the particles do not enter the etching pit, and therefore the particles are substantially present in the area of ​​the carbon coating layer excluding the entry part. However, in the pressing step of the cathode formation process, the particles compress and deform the etching pit, thereby favorably improving the adhesion between the carbon coating layer and the current collector in contact therewith, and favorably reducing the interface resistance between the carbon coating layer and the current collector. In addition, these particles play a role of suitably pushing carbon particles having a particle size capable of entering the etching pits into the etching pits during the pressing step of the cathode formation process. Meanwhile, the carbon particles having a particle size capable of entering the etching pits are filled not only in the entry parts of the carbon coating layer, but also in the gaps between the large carbon particles present only in the areas other than the entry parts, and are present throughout the carbon coating layer. Note that the term "carbon particles" refers to particles recognized as a single structural element in the carbon coating layer, and may be primary particles, secondary particles, or higher order particles, and the term "particle size" refers to the particle size of the primary particles, the particle size of the secondary particles, or the particle size of the higher order particles, depending on the form of the above-mentioned particles.

[0018] Carbon particles for forming the carbon coating layer can be used without any particular limitation in various shapes such as fibrous, spherical, and scaly. Examples of such carbon particles include porous carbon such as carbon nanotubes, carbon nanofibers, carbon nanohorns, and activated carbon, carbon black such as ketjen black, furnace black, channel black, and acetylene black, amorphous carbon, natural graphite, artificial graphite, graphitized ketjen black, and mesoporous carbon. When the carbon coating layer contains carbon particles having a particle size that cannot enter the etching pit, the carbon particles may be composed of the same type of carbon. In other words, the carbon coating layer may be formed using the same type of carbon having a wide particle size distribution, for example, acetylene black having a wide particle size distribution. In this case, among the same type of carbon, carbon particles having a particle size that cannot enter the etching pit play the above-mentioned role. In addition, a wide particle size distribution of carbon particles may be obtained by using a mixture of different types of carbon, for example, a mixture of scaly graphite and acetylene black. When the carbon particles having a particle size that makes it impossible for them to enter the etching pits are composed of flake graphite, the flake graphite particles are oriented so that their basal planes overlap with each other, which easily compresses and deforms the etching pits, and they easily break through the oxide layer and become conductive with the cathode substrate. When flake graphite and carbon black are used in combination, the carbon black is easily pushed into the etching pits and between the flake graphite particles, forming a carbon coating layer that is particularly dense, has excellent electrical conductivity, and is excellent in adhesion to the current collector, resulting in a solid electrolytic capacitor that is particularly excellent in high frequency characteristics and high temperature stability. Effect of the Invention

[0019] The solid electrolytic capacitor of the present invention exhibits high capacitance, low ESR, excellent high frequency characteristics and high high temperature durability. [Brief description of the drawings]

[0020] [Figure 1]FIG. 2 is a conceptual diagram showing an enlarged schematic view of a region near a carbon coating layer in a cross section of a cathode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The solid electrolytic capacitor of the present invention comprises: a cathode comprising: a cathode substrate made of a valve metal and having an etching pit; an oxide layer made of an oxide of the valve metal provided on a surface of the cathode substrate; and a carbon coating layer provided on a surface of the oxide layer, containing carbon particles, and having an entry portion that enters the etching pit and a penetration portion that penetrates the oxide layer and is electrically connected to the cathode substrate; an anode having an anode substrate made of a valve metal and a dielectric layer made of an oxide of the valve metal constituting the anode substrate and provided on a surface of the anode substrate; a solid electrolyte layer including a conductive polymer and disposed between the carbon coating layer of the cathode and the dielectric layer of the anode; The above-mentioned special carbon coating layer acts to provide the solid electrolytic capacitor with high capacitance, low ESR, excellent high frequency characteristics, and high temperature durability. This solid electrolytic capacitor can be manufactured by a method including the following cathode formation step, anode formation step, and electrolyte formation step. Each step will be described in detail below.

[0022] (1) Cathode formation process The cathode formation process includes a coating step of coating a surface of an oxide layer made of an oxide of a valve metal provided on the surface of a cathode substrate made of a valve metal and having etching pits, and drying the carbon slurry to form a slurry layer, and a pressing step of applying a pressing treatment to the slurry layer to press the carbon particles into the etching pits and cause the carbon particles to break through the oxide layer, thereby forming a carbon coating layer having an entry portion that enters the etching pits and a penetration portion that penetrates the oxide layer and is conductive with the cathode substrate.

[0023] The cathode substrate can be any substrate made of valve metal and having etching pits, which is used as a cathode substrate in conventional solid electrolytic capacitors, without any particular limitation. For example, foil made of valve metal such as aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony, which is subjected to chemical or electrochemical etching to increase the surface area, is preferably aluminum foil. The etching pits in the cathode substrate can be tunnel pits or spongy pits, or can be through-type pits or residual core-type pits, and are appropriately selected according to the application of the solid electrolytic capacitor. These etching pits can be formed by known AC electrolysis and DC electrolysis.

[0024] The oxide layer provided on the surface of the cathode substrate may be a natural oxide film that is generally present on the surface of the cathode substrate. In addition, a chemical conversion oxide film may be formed on the surface of the cathode substrate by a chemical conversion treatment using a chemical conversion liquid such as an aqueous solution of ammonium borate, an aqueous solution of ammonium adipate, or an aqueous solution of ammonium phosphate, and this chemical conversion oxide film may be used as the oxide layer.

[0025] The carbon slurry used in the coating step contains at least carbon particles, a binder, and a dispersion medium.

[0026] As the carbon particles, carbon particles having various shapes such as fibrous, spherical, and scaly can be used without any particular limitation. Examples of the carbon particles include porous carbon such as carbon nanotubes, carbon nanofibers, carbon nanohorns, and activated carbon, carbon black such as Ketjen black, furnace black, channel black, and acetylene black, amorphous carbon, natural graphite, artificial graphite, graphitized Ketjen black, and mesoporous carbon. These carbon particles may be used alone or in a mixture of two or more kinds. However, the carbon slurry for forming a carbon coating layer having an intrusion portion that intrudes into the etching pit naturally contains at least carbon particles having a particle size that can intrude into the etching pit of the cathode substrate. In a preferred embodiment, carbon particles having a particle size that cannot intrude into the etching pit of the cathode substrate are further contained. In this preferred embodiment, the carbon particles may be composed of the same type of carbon, in other words, the same type of carbon having a wide particle size distribution, such as acetylene black having a wide particle size distribution, may be used, or a mixture of different types of carbon, such as a mixture of flake graphite and acetylene black, may be used to obtain a wide particle size distribution of the carbon particles.

[0027] As the binder, known binders such as polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, carboxymethyl cellulose, styrene butadiene rubber, etc. can be used alone or in combination of two or more. As the dispersion medium, any dispersion medium that does not adversely affect other components, such as N-methylpyrrolidone, dimethylformamide, tetrahydrofuran, isopropyl alcohol, water, etc., can be used without any particular limitation.

[0028] There is no particular limitation on the wet mixing method of carbon particles, binder, and dispersion medium to obtain carbon slurry, and it may be performed by hand mixing using a mortar, or may be performed using a known mixing device such as a stirrer or homogenizer. There is no particular limitation on the mixing time as long as a uniform carbon slurry is obtained. The carbon particles and binder are generally contained in a mass ratio in the range of 80:20 to 95:5.

[0029] The obtained carbon slurry is applied to the surface of the oxide layer provided on the surface of the cathode substrate by a known application method such as a doctor blade method or a casting method under normal pressure or reduced pressure, and then dried to form a slurry layer. Next, a pressing step is performed in which pressure is applied to the obtained slurry layer to form a carbon coating layer.

[0030] 1 is a conceptual diagram showing an enlarged schematic view of a cross section of a cathode 10 formed using a cathode substrate 11 having residual-core type spongy pits, showing a region near a carbon coating layer 13. The solid electrolytic capacitor of the present invention is characterized in that the carbon coating layer 13 in the cathode 10 has an intrusion portion 13a that intrudes into the etching pit 11a and a penetration portion 13b that penetrates the oxide layer 12 and is electrically connected to the cathode substrate 11.

[0031] Before applying the carbon slurry, a base layer made of a conductive inorganic material such as carbon, titanium nitride, or titanium carbide may be provided on the surface of the oxide layer by a deposition method such as vacuum deposition or ion plating. The base layer formed by the deposition method is formed only on the surface of the oxide layer on the outer surface of the cathode substrate (the surface on which no etching pits are formed; indicated by 11b in FIG. 1), but not on the surface of the oxide layer on the surfaces of the etching pits (indicated by 11c in FIG. 1).

[0032] The pressing step can be performed by a roll press or a vertical press, and it is necessary to apply pressure to push the carbon particles into the etching pits of the cathode substrate and to make the carbon particles break through the oxide layer. If a base layer is provided on the outer surface of the cathode substrate, it is necessary to apply pressure to make the carbon particles break through the base layer and the oxide layer. Whether or not the carbon particles have broken through the oxide layer can be easily determined by a preliminary experiment investigating the correlation between the interface resistance and pressure in the cathode. When the above interface resistance is 10 mΩ cm 2 Less than 6mΩcm, preferably 2 Less than 3mΩcm, more preferably 2 It is preferable to select a pressure of 0.5 kNcm or less, because this makes it possible to obtain favorable electrical continuity between the carbon coating layer and the cathode substrate and favorable adhesion between the carbon coating layer and the current collector. The pressure during pressing varies depending on the type of pressing device and cathode substrate used, but when pressure is applied by a roll press, it is generally set to 0.5 kNcm. -1 A line pressure of at least this value is adopted.

[0033] Furthermore, if the average length of the penetration parts of the carbon coating layer (Hb in FIG. 1) is 1 / 5 or more, preferably 1 / 4 or more, of the average length of the etching pits (Ha in FIG. 1), the adhesion between the carbon coating layer and the current collector in contact with this carbon coating layer is suitably maintained, the interfacial resistance between the carbon coating layer and the current collector is reduced, and peeling of the carbon coating layer is suitably suppressed, which is preferable.

[0034] When the carbon coating layer contains carbon particles having a particle size that makes it impossible for the carbon particles to enter the etching pits, the particles are substantially present in the region of the carbon coating layer excluding the entry portion, and in the pressing step, the particles compress and deform the etching pits, thereby favorably improving the adhesion between the carbon coating layer and the current collector in contact therewith, favorably reducing the interface resistance between the carbon coating layer and the current collector, and also favorably pushing the carbon particles having a particle size capable of entering the etching pits into the etching pits. On the other hand, the carbon particles having a particle size capable of entering the etching pits are filled not only in the entry portion of the carbon coating layer, but also in the gaps between the large carbon particles present only in the region excluding the entry portion, and are present throughout the entire carbon coating layer.

[0035] When the carbon particles having a particle size that cannot enter the etching pits are composed of flake graphite, the flake graphite particles are oriented so that their basal planes overlap with each other, which makes it easy to compress and deform the etching pits and to break through the oxide layer to establish electrical contact with the cathode substrate. When flake graphite and carbon black are used in combination, the carbon black is easily pushed into the etching pits and between the flake graphite particles, forming a carbon coating layer that is particularly dense, has excellent electrical conductivity, and is excellent in adhesion to the current collector, resulting in a solid electrolytic capacitor that is particularly excellent in high frequency characteristics and high temperature stability. The flake graphite and carbon black are generally contained in a mass ratio of 90:10 to 25:75.

[0036] (2)Anode formation process In the anode formation step, the surface of the anode substrate made of a valve metal is oxidized to form a dielectric layer. As the anode substrate, a substrate made of a valve metal that is used as an anode substrate in a conventional solid electrolytic capacitor can be used without any particular limitation. For example, a foil made of a valve metal such as aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, or antimony, which has been subjected to a chemical or electrochemical etching process to increase the surface area, can be used, and aluminum foil is particularly preferred. The etching pits in the anode substrate may be tunnel pits or spongy pits, or may be through-type pits or residual core-type pits, and are appropriately selected according to the application of the solid electrolytic capacitor. These etching pits can be formed by known AC electrolysis and DC electrolysis. The dielectric layer on the surface of the anode substrate can be formed by a known method of subjecting the anode substrate to a chemical conversion treatment using a chemical conversion solution such as an aqueous solution of ammonium borate, an aqueous solution of ammonium adipate, or an aqueous solution of ammonium phosphate.

[0037] (3) Electrolyte formation process In the electrolyte forming step, the carbon coating layer of the cathode and the dielectric layer of the anode are opposed to each other, and a solid electrolyte layer containing a conductive polymer is formed between them. A separator is usually disposed between the carbon coating layer of the cathode and the dielectric layer of the anode, and the solid electrolyte layer in contact with both the carbon coating layer of the cathode and the dielectric layer of the anode is held by this separator. For example, the belt-shaped cathode and anode are laminated with the separator between them so that the carbon coating layer of the cathode and the dielectric layer of the anode face each other, and then the laminate is wound to form a capacitor element, and then a solid electrolyte layer can be formed. In addition, the cathode and anode of a desired shape are laminated with the separator between them so that the carbon coating layer of the cathode and the dielectric layer of the anode face each other to form a capacitor element, and then a solid electrolyte layer can be formed. In addition, a plurality of sets of cathodes and anodes are alternately laminated with the separator between them so that the carbon coating layer of the cathode and the dielectric layer of the anode face each other to form a capacitor element, and then a solid electrolyte layer can be formed. As the separator, a woven or nonwoven fabric made of cellulose-based fibers, for example, Manila paper, Kraft paper, Esparto paper, hemp paper, cotton paper, rayon, and mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and the like, glass paper, and mixed papers of glass paper with Manila paper or Kraft paper can be used.

[0038] As a monomer for obtaining a conductive polymer, any monomer having a π-conjugated double bond that has been used for the production of a conventional conductive polymer can be used without any particular limitation. Representative monomers are shown below. These monomers may be used alone or as a mixture of two or more kinds.

[0039] First, thiophene and thiophene derivatives, for example, 3-alkylthiophenes such as 3-methylthiophene and 3-ethylthiophene, 3,4-dialkylthiophenes such as 3,4-dimethylthiophene and 3,4-diethylthiophene, 3-alkoxythiophenes such as 3-methoxythiophene and 3-ethoxythiophene, 3,4-dialkoxythiophenes such as 3,4-dimethoxythiophene and 3,4-diethoxythiophene, 3,4-alkylenedioxythiophenes such as 3,4-methylenedioxythiophene, 3,4-ethylenedioxythiophene and 3,4-(1,2-propylenedioxy)thiophene, 3,4-alkyleneoxythiathiophenes such as thiophene, 3,4-methyleneoxythiathiophene, 3,4-ethyleneoxythiathiophene, and 3,4-(1,2-propyleneoxythia)thiophene; 3,4-alkylenedithiathiophenes such as 3,4-methylenedithiathiophene, 3,4-ethylenedithiathiophene, and 3,4-(1,2-propylenedithia)thiophene; and alkylthieno[3,4-b]thiophenes such as thieno[3,4-b]thiophene, isopropylthieno[3,4-b]thiophene, and t-butyl-thieno[3,4-b]thiophene.

[0040] Further examples include pyrrole and pyrrole derivatives, for example, N-alkylpyrroles such as N-methylpyrrole and N-ethylpyrrole, 3-alkylpyrroles such as 3-methylpyrrole and 3-ethylpyrrole, 3-alkoxypyrroles such as 3-methoxypyrrole and 3-ethoxypyrrole, 3,4-dialkylpyrroles such as N-phenylpyrrole, N-naphthylpyrrole, 3,4-dimethylpyrrole and 3,4-diethylpyrrole, and 3,4-dialkoxypyrroles such as 3,4-dimethoxypyrrole and 3,4-diethoxypyrrole. Further examples include aniline and aniline derivatives, such as 2,5-dialkylanilines such as 2,5-dimethylaniline and 2-methyl-5-ethylaniline, 2,5-dialkoxyanilines such as 2,5-dimethoxyaniline and 2-methoxy-5-ethoxyaniline, 2,3,5-trialkoxyanilines such as 2,3,5-trimethoxyaniline and 2,3,5-triethoxyaniline, 2,3,5,6-tetraalkoxyanilines such as 2,3,5,6-tetramethoxyaniline and 2,3,5,6-tetraethoxyaniline, and furan and furan derivatives, such as 3-alkylfurans such as 3-methylfuran and 3-ethylfuran, 3,4-dialkylfurans such as 3,4-dimethylfuran and 3,4-diethylfuran, 3-alkoxyfurans such as 3-methoxyfuran and 3-ethoxyfuran, and 3,4-dialkoxyfurans such as 3,4-dimethoxyfuran and 3,4-diethoxyfuran.

[0041] As the monomer, it is preferable to use a monomer selected from the group consisting of thiophenes having substituents at the 3rd and 4th positions. The substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the 3rd and 4th carbons. In particular, 3,4-(ethylenedioxythiophene) is preferable because it gives a conductive polymer that exhibits high conductivity and excellent heat resistance.

[0042] The solid electrolyte layer may be formed by electrolytic polymerization or chemical polymerization, or may be formed using a dispersion liquid containing at least conductive polymer particles and a dispersion medium.

[0043] The electrolytic polymerization is carried out by introducing the capacitor element into a polymerization solution containing at least a monomer, a supporting electrolyte, and a solvent, and applying a voltage between the anode and the cathode. In the process of electrolytic polymerization, anions released from the supporting electrolyte are contained in the conductive polymer layer as dopants. As the solvent for the electrolytic polymerization solution, any solvent that can dissolve a desired amount of monomer and supporting electrolyte and does not adversely affect the electrolytic polymerization can be used without any particular limitation. Examples include water, methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, butyronitrile, acetone, methyl ethyl ketone, tetrahydrofuran, 1,4-dioxane, γ-butyrolactone, methyl acetate, ethyl acetate, methyl benzoate, ethyl benzoate, ethylene carbonate, propylene carbonate, nitromethane, nitrobenzene, sulfolane, and dimethyl sulfolane. These solvents may be used alone or in a mixture of two or more.

[0044] As the supporting electrolyte contained in the polymerization solution for electrolytic polymerization, a compound that releases a dopant contained in a conventional conductive polymer can be used without any particular limitation. For example, in addition to inorganic acids such as boric acid, nitric acid, phosphoric acid, and organic acids such as acetic acid, oxalic acid, and citric acid, sulfonic acids such as methanesulfonic acid, dodecylsulfonic acid, and p-toluenesulfonic acid, and salts thereof can be exemplified. In addition, polycarboxylic acids such as polyacrylic acid, polymethacrylic acid, and polymaleic acid, polysulfonic acids such as polystyrenesulfonic acid and polyvinylsulfonic acid, and salts thereof can also be used as the supporting electrolyte. Furthermore, boron complexes such as borodisalicylic acid, borodioxalic acid, and borodimalonic acid, sulfonylimic acid, and salts thereof can also be used as the supporting electrolyte. Examples of salts include alkali metal salts such as lithium salts, sodium salts, and potassium salts, and alkyl ammonium salts such as ammonium salts, ethylammonium salts, and butylammonium salts. These supporting electrolytes may be used alone or in combination of two or more. Depending on the type of supporting electrolyte, they are used in an amount not exceeding their saturation solubility in the polymerization solution and at a concentration at which a sufficient current can be obtained for electrolytic polymerization.

[0045] The electrolytic polymerization is carried out by any of the methods of the constant potential method, the constant current method, and the potential sweep method. In the case of the constant potential method, although it depends on the type of monomer, a potential of 1.0 to 1.5 V against a saturated calomel electrode is suitable, and in the case of the constant current method, although it depends on the type of monomer, a potential of 1 to 10,000 μA / cm is suitable. 2 In the case of the potential sweep method, it is preferable to sweep the range of 0 to 1.5 V against a saturated calomel electrode at a rate of 5 to 200 mV / sec, although this depends on the type of monomer. There is no strict limit to the polymerization temperature, but it is generally in the range of 10 to 60°C. There is also no strict limit to the polymerization time, but it is generally in the range of 1 minute to 10 hours.

[0046] The formation of the solid electrolyte layer by chemical polymerization can be performed by preparing a solution in which both a monomer and an oxidizing agent are dissolved in a solvent, impregnating the gap between the carbon coating layer of the cathode and the dielectric layer of the anode, and then drying the solution, or by preparing a solution in which a monomer is dissolved in a solvent and a solution in which an oxidizing agent is dissolved in a solvent, impregnating the gap between the carbon coating layer of the cathode and the dielectric layer of the anode alternately, and then drying the solution. Examples of the solvent that can be used include water, methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, butyronitrile, acetone, methyl ethyl ketone, tetrahydrofuran, 1,4-dioxane, γ-butyrolactone, methyl acetate, ethyl acetate, methyl benzoate, ethyl benzoate, ethylene carbonate, propylene carbonate, nitromethane, nitrobenzene, sulfolane, and dimethyl sulfolane. These solvents may be used alone or in combination of two or more.

[0047] As the oxidizing agent, trivalent iron salts such as p-toluenesulfonate iron(III), naphthalenesulfonate iron(III), anthraquinonesulfonate iron(III), or persulfates such as ammonium peroxodisulfate and sodium peroxodisulfate can be used, and a single compound or two or more compounds can be used. There is no strict limit to the polymerization temperature, but it is generally in the range of 10 to 60°C. There is no strict limit to the polymerization time, but it is generally in the range of 1 minute to 10 hours.

[0048] Furthermore, a solid electrolyte layer can be formed by impregnating a dispersion liquid containing at least conductive polymer particles and a dispersion medium between the carbon coating layer of the cathode and the dielectric layer of the anode, followed by drying. The dispersion medium in the dispersion liquid can be, for example, water, methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, butyronitrile, acetone, methyl ethyl ketone, tetrahydrofuran, 1,4-dioxane, γ-butyrolactone, methyl acetate, ethyl acetate, methyl benzoate, ethyl benzoate, ethylene carbonate, propylene carbonate, nitromethane, nitrobenzene, sulfolane, or dimethyl sulfolane, but it is preferable to use water as the dispersion medium.

[0049] The above dispersion liquid can be obtained, for example, by adding a monomer, an acid or a salt thereof that releases a dopant, and an oxidizing agent to water, stirring until chemical oxidation polymerization is completed, then removing the oxidizing agent and residual monomers by purification means such as ultrafiltration, cation exchange, and anion exchange, and then performing dispersion treatments such as ultrasonic dispersion treatment, high-speed fluid dispersion treatment, and high-pressure dispersion treatment as necessary. In addition, a monomer and an acid or a salt thereof that releases a dopant are added to water, electrolytically oxidative polymerization is performed while stirring, and then residual monomers are removed by purification means such as ultrafiltration, cation exchange, and anion exchange, and then performing dispersion treatments such as ultrasonic dispersion treatment, high-speed fluid dispersion treatment, and high-pressure dispersion treatment as necessary. Furthermore, the liquid obtained by the above-mentioned chemical oxidation polymerization method or electrolytic polymerization method is filtered to separate aggregates, thoroughly washed, and then added to water, and subjected to dispersion treatments such as ultrasonic dispersion treatment, high-speed fluid dispersion treatment, and high-pressure dispersion treatment. The content of the conductive polymer particles in the dispersion is generally in the range of 1.0 to 3.0% by mass, and preferably in the range of 1.5 to 2.0% by mass. There is no strict limit to the drying temperature, but it is generally in the range of 50 to 200° C. There is also no strict limit to the drying time, but it is generally in the range of 1 to 10 hours.

[0050] After the electrolyte formation step is completed, the capacitor element with the solid electrolyte layer added is housed in an exterior case and sealed to obtain the solid electrolytic capacitor of the present invention. The method for sealing the capacitor element with the solid electrolyte layer formed thereon may be a method of molding the capacitor element with resin. In the solid electrolytic capacitor of the present invention, the carbon coating layer having the above-mentioned special form provides high capacitance, low ESR, excellent high frequency characteristics, and high high temperature durability.

[0051] In addition, in the solid electrolytic capacitor of the present invention, the solid electrolyte layer can be impregnated with an electrolyte to form a hybrid electrolytic capacitor. The electrolyte improves the capacitance of the capacitor and reduces the ESR. The electrolyte also improves the repair performance of the dielectric oxide film, thereby extending the life of the capacitor. For the hybrid electrolytic capacitor, any electrolyte suitable for low voltage or medium to high voltage can be used without any particular limitation. Examples include electrolytes obtained by dissolving electrolytes such as ammonium salts of borodisalicylic acid, borodisalic acid, borodiglycolic acid, 1,6-decanedicarboxylic acid, azelaic acid, adipic acid, phosphoric acid, boric acid, etc., quaternary ammonium salts, quaternary amidinium salts, and amine salts at a predetermined concentration in a solvent such as γ-butyrolactone, ethylene glycol, polyoxyethylene glycol, sulfolane, polycarbonate, and mixtures thereof. EXAMPLES

[0052] The present invention will be described with reference to the following examples, but the present invention is not limited to the following examples.

[0053] Example 1 As a cathode substrate for obtaining a cathode, an aluminum foil was used in which spongy etching pits were formed with an etching ratio (ratio of actual surface area to projected area) of 22. This aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and the surface of the aluminum foil was subjected to a chemical conversion voltage of 1.2 V. fs A chemical oxide film (oxide layer) was formed.

[0054] The carbon particles used were flake graphite with an average particle size of 4 μm and carbon black with an average primary particle size of 50 nm and an average secondary particle size of 0.3 μm. A mixture of these in a mass ratio of 75:25 was mixed with styrene butadiene rubber and an aqueous solution of sodium carboxymethylcellulose in a mass ratio of 84:10:6, and the mixture was dispersed with a stirrer to prepare a carbon slurry.

[0055] The obtained carbon slurry was applied onto the above-mentioned chemical oxide film and dried to form a slurry layer. A linear pressure of 5.38 kNcm was applied to this slurry layer. -1 A carbon coating layer with a thickness of 1 μm was formed by pressing the substrate with a roll press of 100 mm. 2 A cathode for a solid electrolytic capacitor was obtained by punching out the cathode. When the cross section of the cathode was observed by SEM photography, it was found that the carbon black had penetrated to a position of about 1 / 3 of the length of the etching pit. In addition, in the region other than the penetration part of the carbon coating layer, the flake graphite was oriented so that the basal planes of the graphite overlapped with each other, and the carbon black was filled between the graphite. Furthermore, the carbon slurry was applied to the carbon coating layer of the cathode for the solid electrolytic capacitor and dried to prepare a confirmation cathode having a carbon coating layer with a thickness of 20 μm. The interface resistance of this cathode was measured using an electrode resistance measurement system (manufactured by Hioki Electrochemical Co., Ltd., model number RM2610), and was found to be 1.63 mΩcm. 2 From this value, it was determined that the carbon coating layer of the cathode for the solid electrolytic capacitor was electrically connected to the aluminum of the cathode substrate.

[0056] An aluminum foil with sponge-like etching pits formed thereon was used as an anode substrate for obtaining an anode. This aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium adipate, and the surface of the aluminum foil was subjected to a chemical conversion voltage of 45.6 V. fs The aluminum foil with the dielectric layer added was then placed on a plate with a projected area of ​​2.1 cm. 2 The current density was 0.2 mAcm using an aqueous solution of ammonium dihydrogen phosphate as the formation solution. -2 The end surface portions formed during punching were repaired by chemical conversion treatment under the above conditions for 10 minutes, thereby obtaining an anode for a solid electrolytic capacitor.

[0057] An aluminum terminal was ultrasonically connected to each of the obtained anode and cathode, and the dielectric layer of the anode and the carbon coating layer of the cathode were placed opposite each other via a zigzag folded separator and fixed with imide tape to obtain a capacitor element.

[0058] Fine particles of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid were dispersed in a dispersion medium of water with 5% ethylene glycol to obtain a dispersion liquid for forming a solid electrolyte layer. The above capacitor element was impregnated with the obtained dispersion liquid under a pressure of 30 kPa for 120 seconds, and dried at 110°C for 120 minutes. The capacitor element with the added solid electrolyte layer was then sealed with a laminate material to obtain a solid electrolytic capacitor with a rated voltage of 25 WV.

[0059] The obtained fixed electrolytic capacitor was subjected to aging treatment for 60 minutes by applying a voltage of 28.8V under the condition of 105°C, and then the capacitance at 120Hz and 10kHz and the ESR at 10kHz and 100kHz were measured as the initial characteristics of the capacitor under the condition of 20°C. Next, 500 cycles of charge and discharge were repeated under the high temperature condition of 105°C as a durability test, and then the capacitance at 120Hz and 10kHz and the ESR at 10kHz and 100kHz were measured again under the condition of 20°C as the characteristics after the durability test. The charge and discharge were performed between 25V and 0V, with a charge current of 20mA for 10 seconds, and with a discharge resistance of 0Ω (no resistance) for 10 seconds.

[0060] Comparative Example 1 The procedure of Example 1 was repeated, except that the slurry layer was not subjected to pressing treatment during the cathode formation process. The carbon coating layer of the cathode for the solid electrolytic capacitor had a thickness of 1 μm. In addition, when the cross section of the cathode was observed by SEM photography, almost no carbon particles were observed in the etching pits. Furthermore, the interface resistance value of a test cathode having a carbon coating layer with a thickness of 20 μm obtained by applying the carbon slurry onto the carbon coating layer of the cathode for the solid electrolytic capacitor and drying it was 31.2 mΩcm. 2 It was determined that the carbon coating layer of the cathode for the solid electrolytic capacitor was not electrically connected to the aluminum of the cathode substrate.

[0061] Example 2 The procedure of Example 1 was repeated, except that the carbon slurry used to form the carbon coating layer on the cathode was prepared using only carbon black with an average primary particle size of 35 nm and an average secondary particle size of 0.3 μm as the carbon particles. The thickness of the carbon coating layer on the cathode for the solid electrolytic capacitor was 1 μm. In addition, when the cross section of the cathode was observed using an SEM photograph, the carbon black had penetrated to a position about 1 / 3 of the length of the etching pit. Furthermore, the interface resistance value of the confirmation cathode having a carbon coating layer with a thickness of 20 μm obtained by applying the carbon slurry on the carbon coating layer of the cathode for the solid electrolytic capacitor and drying it was 1.83 mΩcm. 2 It was determined that the carbon coating layer of the cathode for the solid electrolytic capacitor was electrically connected to the aluminum of the cathode substrate.

[0062] Comparative Example 2 The procedure of Example 2 was repeated, except that the slurry layer was not pressed during the cathode formation process. The carbon coating layer of the cathode for the solid electrolytic capacitor had a thickness of 1 μm. In addition, when the cross section of the cathode was observed using an SEM photograph, the intrusion of carbon particles was observed only near the opening of the etching pit. Furthermore, the interface resistance value of a test cathode having a carbon coating layer with a thickness of 20 μm obtained by applying the carbon slurry onto the carbon coating layer of the cathode for the solid electrolytic capacitor and drying it was 19.7 mΩcm. 2 It was determined that the carbon coating layer in the cathode for the solid electrolytic capacitor was not electrically connected to the aluminum of the cathode substrate.

[0063] Comparative Example 3 An aluminum foil with spongy etching pits formed at an etching ratio of 70 was used as a cathode substrate for obtaining a cathode. This aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and the surface of the aluminum foil was subjected to a chemical conversion voltage of 3 V. fs After forming a chemical oxide film (oxide layer) of 2.1 cm2 2A cathode for a solid electrolytic capacitor was obtained by punching out the cathode and the anode and dispersion liquid used in Example 1. The characteristics of the obtained solid electrolytic capacitor were evaluated under the same conditions as those shown in Example 1.

[0064] Comparative Example 4 As a cathode substrate for obtaining a cathode, an aluminum foil on which spongy etching pits were formed at an etching ratio of 7 or less was used. This aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and the surface of the aluminum foil was subjected to a chemical conversion voltage of 5 V. fs A chemical oxide film (oxide layer) of 2.1 cm2 was then formed. Next, instead of the carbon coating layer, a vapor-deposited film of titanium carbide was formed on the surface of the chemical oxide film by arc ion plating. 2 A cathode for a solid electrolytic capacitor was obtained by punching out the cathode. The titanium carbide vapor deposition film did not penetrate into the etching pits. A solid electrolytic capacitor was produced using this cathode and the anode and dispersion used in Example 1, and the characteristics of the obtained solid electrolytic capacitor were evaluated under the same conditions as those shown in Example 1.

[0065] Comparative Example 5 An aluminum foil without etched pits was used as a cathode substrate to obtain a cathode. In this example, a chemical oxide film was not formed, and a natural oxide film was used as the oxide layer. Next, instead of a carbon coating layer, a vapor-deposited film made of carbon was formed on the surface of the natural oxide film by sputtering, and then a 2.1 cm2 projected area was measured. 2 A cathode for a solid electrolytic capacitor was obtained by punching out the cathode and the anode and dispersion liquid used in Example 1. A solid electrolytic capacitor was produced using this cathode and the anode and dispersion liquid used in Example 1, and the characteristics of the obtained solid electrolytic capacitor were evaluated under the same conditions as those shown in Example 1.

[0066] Table 1 shows the capacitance values ​​at 20° C. obtained for the solid electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 to 5, and Table 2 shows the ESR values ​​at 20° C. obtained for the solid electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 to 5. In the tables, carbon black is represented as CB. [Table 1]

[0067] [Table 2]

[0068] The titanium carbide vapor deposition film present on the cathode of the capacitor of Comparative Example 4, the carbon vapor deposition film present on the cathode of the capacitor of Comparative Example 5, and the carbon coating layer present on the cathode of the capacitor of Comparative Examples 1 and 2, which is formed by applying a carbon slurry but is not pressed, have been conventionally known as coating layers that increase the capacitance of the capacitor by bringing the cathode capacitance close to infinity and suppress the growth of an aluminum oxide film on the cathode (see Patent Documents 2 to 4). When the capacitance and ESR of the capacitors of Comparative Examples 1 and 2 are compared with the capacitance and ESR of the capacitor of Comparative Example 3, which has a cathode without a coating layer, it is true that the change in capacitance and ESR before and after the charge / discharge test is small, and the capacitance at 120 Hz is high, but the capacitance at 10 kHz is rather decreased, and there is a problem with the high-frequency characteristics. In contrast, the capacitors of Comparative Examples 1 and 2 showed an ESR even lower than that of the capacitors of Comparative Examples 4 and 5, but also had a low capacitance at 10 kHz and a problem with the high-frequency characteristics.

[0069] In contrast, in the capacitors of Examples 1 and 2, which have a cathode having a carbon coating layer formed through the application of a carbon slurry and pressed, the ESR value is significantly reduced under both 10 kHz and 100 kHz conditions, as can be clearly understood by comparing the ESR of the capacitor of Example 1 with that of the corresponding capacitor of Comparative Example 1, and comparing the ESR of the capacitor of Example 2 with that of the corresponding capacitor of Comparative Example 2, and the change in ESR before and after the charge / discharge test is almost the same and excellent. The significant decrease in ESR in the capacitors of Examples 1 and 2 is considered to be due to the improvement in adhesion between the carbon coating layer and the current collector in contact therewith, which reduces the interface resistance therebetween. In addition, as can be clearly understood by comparing the capacitance of the capacitor of Example 1 with that of the corresponding capacitor of Comparative Example 1, and comparing the capacitance of the capacitor of Example 2 with that of the corresponding capacitor of Comparative Example 2, the capacitance of the capacitors of Examples 1 and 2 is increased under both 120 Hz and 10 kHz conditions, and the change in capacitance at 10 kHz before and after the charge / discharge test is also improved, and the high-frequency characteristics are improved.

[0070] Patent documents 1 to 4 have already shown that a coating layer can be used to increase the capacitance of a capacitor by bringing the cathode capacitance close to infinity, but the measurements have been carried out exclusively under conditions of 120 Hz, and no information has been given on the capacitance in the high frequency range (10 kHz). As can be seen from the capacitance of the capacitors in Comparative Examples 1 to 5, the measures in these prior documents do not increase the capacitance in the high frequency range (10 kHz).

[0071] It is considered that the capacitance in the high frequency region (10 kHz) is determined by the magnitude relationship between the interface resistance (interface resistance measured between the solid electrolyte layer and the cathode substrate and dependent on all interfaces included in the above components) in the components consisting of the cathode and the solid electrolyte layer, and the oxide film (oxide layer) resistance in the current collector. In the capacitors in Comparative Examples 1 and 2 in which the pressing process is not performed to form the carbon coating layer, the interface resistance between the current collector and the carbon coating layer is large, so the former is larger than the latter, and as a result, the effect of the cathode capacitance generated by the oxide film in the current collector appears, and the capacitor capacitance is low. In the capacitors in Examples 1 and 2 in which the pressing process is performed to form the carbon coating layer, the interface resistance between the current collector and the carbon coating layer is small, so the former is smaller than the latter, and as a result, the effect of the cathode capacitance caused by the oxide film in the current collector does not appear, and the capacitor capacitance is high.

[0072] Comparing the characteristics of the capacitor of Example 1 with those of the capacitor of Example 2, it is found that the ESR of the capacitor of Example 1 is particularly low, the capacitance at 10 kHz of the capacitor of Example 1 is particularly high, and the change in capacitance before and after the charge / discharge test is particularly small, and the capacitor of Example 1 is particularly excellent in high frequency characteristics and high temperature stability. This is believed to be because the flake graphite, which is substantially only present in the region excluding the entry portion of the carbon coating layer, is oriented so that the basal planes of the graphite overlap with each other, which easily compresses and deforms the etching pits and easily breaks through the oxide layer to establish electrical conduction with the cathode base, and the carbon black is easily pushed into the etching pits and between the flake graphite, forming a carbon coating layer that is dense, has excellent electrical conductivity, and has excellent adhesion to the current collector. [Industrial Applicability]

[0073] According to the present invention, a solid electrolytic capacitor having high capacitance, low ESR, excellent high frequency characteristics and high high temperature durability can be obtained. [Explanation of symbols]

[0074] 10 cathode 11 Cathode substrate 11a Etching pit 11b Outer surface 11c Etching pit surface 12 Oxide layer 13 Carbon coating layer 13a Entrance section 13b Penetration Ha Length of etching pit Hb entry length

Claims

1. a cathode comprising: a cathode substrate made of a valve metal and having an etching pit; an oxide layer made of an oxide of the valve metal provided on a surface of the cathode substrate; and a carbon coating layer provided on a surface of the oxide layer, containing carbon particles, and having an entry portion that enters the etching pit and a penetration portion that penetrates the oxide layer and is electrically connected to the cathode substrate; an anode having an anode substrate made of a valve metal and a dielectric layer made of an oxide of the valve metal constituting the anode substrate and provided on a surface of the anode substrate; a solid electrolyte layer including a conductive polymer and disposed between the carbon coating layer of the cathode and the dielectric layer of the anode; A solid electrolytic capacitor comprising:

2. 2. The solid electrolytic capacitor of claim 1, wherein the carbon coating layer includes carbon particles having a particle size that makes it impossible for the carbon particles to penetrate into the etch pits.

3. 3. The solid electrolytic capacitor according to claim 1, wherein the carbon particles in the carbon coating layer are made of the same type of carbon.

4. 3. The solid electrolytic capacitor according to claim 2, wherein the carbon particles having a particle size that makes it impossible for them to enter the etching pits in the carbon coating layer are composed of flake graphite.

5. 5. The solid electrolytic capacitor according to claim 1, wherein an average length of the penetration portions of the carbon coating layer is at least 1 / 5 of an average length of the etching pits.

6. The interface resistance at the cathode is 10 mΩ cm 2 The solid electrolytic capacitor according to any one of claims 1 to 5, wherein:

7. a coating step of coating a surface of an oxide layer made of an oxide of a valve metal provided on a surface of a cathode substrate made of a valve metal and having etching pits, and drying the carbon slurry to form a slurry layer; and a pressing step of applying a pressing treatment to the slurry layer to press the carbon particles into the etching pits and cause the carbon particles to break through the oxide layer, thereby forming a carbon coating layer having an intrusion portion intruding into the etching pits and a penetration portion penetrating the oxide layer and conducting to the cathode substrate, an anode forming step of forming a dielectric layer by oxidizing the surface of an anode substrate made of a valve metal; An electrolyte forming step of forming a solid electrolyte layer containing a conductive polymer between the carbon coating layer of the cathode and the dielectric layer of the anode.

2. A method for producing a solid electrolytic capacitor comprising the steps of:

8. 8. The method for producing a solid electrolytic capacitor according to claim 7, wherein the carbon slurry contains carbon particles having a particle size that makes it impossible for the carbon particles to enter the etching pits.

Citation Information

Patent Citations

  • Cathode foil, production technology thereof and liquid-state aluminum electrolytic capacitor

    CN109950046A

  • Electric double layer capacitor

    JP1999121301A

  • Solid electrolytic capacitor and its manufacture

    JP2000114109A

  • Manufacturing method of electrode metal material and manufacturing method of capacitor using the same

    JP2001297952A

  • Solid electrolytic capacitor

    JP2005109272A